Community perspective analysis of Yogyakarta special region using K-means algorithm - Berlina, Laila Indah; Aesyi, Ulfi Saidata; Kharisma, Kharisma (Emerging Information Science and Technology, 2024)
This study explores community perspectives on Yogyakarta, a culturally rich region in Indonesia known as "Jogja Istimewa," "Student City," and "City of Tourism." Given the potential challenges faced by the region, the research employs the K-Means Algorithm to analyze opinions gathered from Twitter, offering a novel alternative to traditional surveys. Using a data crawling method, relevant tweets about Yogyakarta were collected and processed through preprocessing and TF-IDF to enhance word significance. The findings reveal diverse community views regarding job opportunities, culture, tourism, religious activities, stakeholder involvement, and security. The application of K-Means clustering effectively highlights the multifaceted perspectives of Yogyakarta's residents, providing valuable insights for understanding the region’s socio-cultural dynamics.